The Use of Google Classroom in Facial Skin Care Courses with Technology: Penggunaan Google Classroom pada Mata Kuliah Perawatan Kulit Wajah dengan Teknologi - Putri, Hasri Mutiara; Arum, Aniesa Puspa; Ambarwati, Neneng Siti Silfi (RADIANT: Journal of Applied, Social, and Education Studies, 2021)
Learning outcomes are a learning carried out by someone after Â going through the process of learning activities, which uses an assessment tool prepared by the teacher, such as an evaluation test that includes cognitive, affective and psychomotor aspects. This study aims to determine the relationship between student interest in the use of Google Classroom with learning outcomes of facial skin care with technology. This research is a quantitative research with a survey method with a sample of 65 students of the Cosmetology Education study program batch 2020. The data for the X variable (student interest in using Google Classroom) was obtained by distributing questionnaires with a Likert scale. Meanwhile, the Y variable data (Learning Results of Facial Skin Care with Technology) was obtained from Form 06. The results of the analysis with product moment correlation showed that there was no positive and significant relationship between students' interest in learning outcomes of facial skin care with technology. Based on the calculations obtained a significance value of 0.274 which means it is greater than 0.05. So it can be concluded that Ho which reads: "Students' Interest in Using Google Classroom does not have a positive effect on Learning Outcomes of Facial Skin Care with Technology" is accepted. On the other hand, "Students' Interest in Using Google Classroom has a positive effect on Learning Outcomes of Facial Skin Care with Technology" is rejected. The effective contribution was obtained by 1.9% and the remaining 98.1% was not examined in this study. Â  Hasil belajar adalah suatu pembelajaran yang dilakukan oleh seseorang setelah melalui proses kegiatan belajar, dimana menggunakan suatu alat penilaian yang disusun oleh pengajar, seperti tes evaluasi yang meliputi aspek kognitif, afektif dan psikomotor. Penelitian ini bertujuan untuk mengetahui hubungan minat mahasiswa dalam penggunaan Google Classroom dengan hasil belajar perawatan kulit wajah dengan teknologi. Penelitian ini merupakan penelitian kuantitatif dengan metode survei dengan jumlah sampel 65 mahasiswa program studi Pendidikan Tata Rias angkatan 2020. Data untuk variabel X (minat mahasiswa dalam penggunaan Google Classroom) didapat dengan cara penyebaran kuesioner dengan skala likert. Sedangkan, data variabel Y (hasil belajar Perawatan Kulit Wajah dengan Teknologi) didapat dari Form 06. Hasil analisis dengan korelasi product momen menunjukkan tidak terdapat hubungan positif dan signifikan antara minat mahasiswa terhadap hasil belajar perawatan kulit wajah dengan teknologi. Berdasarkan perhitungan diperoleh nilai signifikansi sebesar 0,274 yang berarti lebih besar dari pada 0,05. Sehingga dapat disimpulkan bahwa Ho yang berbunyi: â€œMinat Mahasiswa Dalam Penggunaan Google Classroom tidak berpengaruh positif terhadap Hasil Belajar Perawatan Kulit Wajah dengan Teknologiâ€ diterima. Sebaliknya, â€œMinat Mahasiswa Dalam Penggunaan Google Classroom berpengaruh positif terhadap Hasil belajar Perawatan Kulit Wajah dengan Teknologiâ€ ditolak. Sumbangan efektif diperoleh sebesar 1,9% dan sisanya 98,1% tidak diteliti dalam penelitian ini.